2020
DOI: 10.5334/cstp.320
|View full text |Cite
|
Sign up to set email alerts
|

The Demographics of Citizen Science Participation and Its Implications for Data Quality and Environmental Justice

Abstract: Citizen science programs have been growing in popularity in recent years and can provide various benefits to participants and their communities. We sought to determine whether these benefits are equitably accessible to all by examining potential demographic disparities in participation in our statewide citizen science program. We first explored whether Illinois RiverWatch participants are demographically and geographically representative of Illinois's population. We conducted online surveys of current particip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 33 publications
0
36
0
Order By: Relevance
“…A well-known challenge that citizen science programs face is in recruiting and retaining a diverse cohort of volunteers (Pandya 2012;Fischer et al, 2021). The common profile of a citizen science volunteer is older, white, and well-educated (Blake et al, 2020;Fischer et al, 2021). It can be a struggle to attract younger and demographically diverse volunteers to citizen science programs.…”
Section: Discussionmentioning
confidence: 99%
“…A well-known challenge that citizen science programs face is in recruiting and retaining a diverse cohort of volunteers (Pandya 2012;Fischer et al, 2021). The common profile of a citizen science volunteer is older, white, and well-educated (Blake et al, 2020;Fischer et al, 2021). It can be a struggle to attract younger and demographically diverse volunteers to citizen science programs.…”
Section: Discussionmentioning
confidence: 99%
“…Studies about the attitudes of volunteers helping environmental research have so far been made for various general groups and highly specialized interest groups in environmental monitoring. These studies included volunteers involved in surface water quality (Alender 2016;Blake et al 2020), hobby ornithologists (Evans et al 2005), people helping research online (Raddick et al 2009;Nov et al 2014) and conservationists (Ryan et al 2001;Bruyere and Rappe 2007;Asah and Blahna 2012;Maund et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…4 Citizen scientist beekeepers' assessment of difficulty of different project tasks from 1 (very easy) to 10 (very difficult). Answers are presented as mean ± 95% confidence interval (n = 69 each) education bias towards higher education (Blake et al 2020). Toomey and Domroese (2013) further found that mostly citizens with higher education and moderate to higher income volunteered as "Bee Watchers" in the "Great Pollinator Project" in New York City.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the rise in citizen participation in policy research, the full potential of citizen science has not been fully realized because of challenges related to the translation and use of the data, the sustainability of citizen science efforts, as well as data quality concerns [86]. Critical to improving equity in climate and health plans, an additional concern is that citizen science participants may not necessarily reflect the broader population, therefore inadvertently exacerbating inequities in climate change agenda-setting [89]. Further research is needed to determine how citizen science can optimally be used to help populations mitigate and adapt to the health risks of climate change, as well as ways to include disproportionately affected communities in constructing and executing their own locally relevant research agenda.…”
Section: Community-partnered Research and Citizen Sciencementioning
confidence: 99%